Invariant solutions of integro-differential Vlasov–Maxwell equations in Lagrangian variables by Lie group analysis - Rezvan, Farshad; Özer, Teoman (Elsevier BV, 2010)
zbMATH Open Web Interface contents unavailable due to conflicting licenses.
Keywords: Integro-differential equations; Reduction forms; optimal system; integro-differential equations; Optimal system; Integro-partial differential equations; Computational Mathematics; reduction forms; Computational Theory and Mathematics; Modelling and Simulation; Lie point symmetries; Geometric theory, characteristics, transformations in context of PDEs